Moisture sorption characteristics of full fat and defatted pistachio kernel flour - Bo, Ling; Rui, Li; Haiyan, Gao; Wang, Shaojin (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The sorption isotherms of full-fat (FPKF), partially defatted (PDPKF), and totally defatted (TDPKF) pistachio kernel flour were performed in the range of water activity (aw) from 0.113 to 0.859 at 15°C, 25°C and 35°C, and the applicability of six mathematical models (Smith, Oswin, Henderson, GAB, Halsey and BET) in data prediction was evaluated. Sorption isotherms were type Ⅱ, according to Brunauer’s classification. Equilibrium moisture content (EMC) increased with an increase in aw at constant temperatures. The sorption isotherms of all three flour samples exhibited hysteresis. Significant differences were found among equilibrium data of FPKF, PDPKF and TDPKF samples. TDPKF showed higher hygroscopic characteristics than PDPKF, and PDPKF showed higher hygroscopic characteristics than FPKF at any temperature and aw studied. It was found that the Smith model was the most satisfactory one for representation of the sorption data of full fat sample, but for defatted samples, Halsey was the best model. The average monolayer moisture content (MMC) calculated by GAB model were 2.443-3.781 g/100 g (d.b.), 3.585-4.886 g/100 g (d.b.) and 5.093-6.918 g/100 g (d.b.) for FPKF, PDPKF and TDPKF, respectively. The isosteric sorption heat (Qst) calculated by means of Clausius-Clapeyron equation decreased with increasing moisture content. The Qst values were 44.76-74.67 kJ/mol, 44.75-99.44 kJ/mol and 44.80-133.28 kJ/mol for FPKF, PDPKF and TDPKF, respectively, in the range of moisture content of 2% to 41% (d.b.) at 25°C.Keywords: pistachio kernel flour, equilibrium moisture content, sorption isotherm, isosteric sorption heat, monolayer moisture contentDOI: 10.3965/j.ijabe.20171003.2838Citation: Ling B, Li R, Gao H Y, Wang S J. Moisture sorption characteristics of full fat and defatted pistachio kernel flour. Int J Agric & Biol Eng, 2017; 10(3): 283–294.